Teachers’ evaluation of the textbook: The case of “English for Law Enforcement” textbook at a Police School in Vietnam = Đánh giá của giáo viên về giáo trình "English for Law Enforcement" tại một trường cảnh sát ở Việt Nam. M.A Thesis Linquistics: 60 14 01 11 - Đinh, Thị Phương Thanh (H.: University of Languages and International Studies, 2018)
52 tr.